The influence of COVID-19 pandemic on body mass and cardiopulmonary endurance of Chinese adolescents: a longitudinal follow-up study - Cheng, Hao; Jiao, Long; Liu, Bin (Frontiers in Public Health, 2024)
Background With the spread and spread of COVID-19 around the world, youth’s learning, lifestyle and health have been greatly affected. Based on the current research, there is no adequate analysis of the development of young people’s physique and heart and lung health during COVID-19, and there is a lack of relevant targeted research. The aim of this study was to investigate the changes of BMI and Maximum Oxygen Absorption (VO2max) in 12–14 year old teenagers before and after COVID-19. Method The BMI, 1,000/800 m running time and associated data related to 29,813 individuals between 2019 and 2022 were collected by cluster sampling, and the changes of BMI Z and VO2max before and after the outbreak were analyzed. Moreover, the relationship between BMI and cardiovascular endurance was analyzed by means of multi-linear stepwise regression. Results The covariance analysis models indicated that compared with 2019, adolescent weight, BMI, and 1,000/800 m running time showed varying degrees of growth in 2020, while lung capacity decreased. All indicators achieved rapid rebound in 2021 and 2022 (p < 0.01); the one-way analysis of variance models indicated that The BMI Z score and VO2max of adolescents showed growth and decline in 2020, respectively, and achieved rapid recovery and development in 2021 and 2022 (p < 0.01). The results of the multiple linear stepwise regression analysis indicate that, after the years of BMI Z and novel coronavirus infection were included (△R2 = 0.179), adolescents’ overweight and obesity were positively correlated with the maximum oxygen uptake (B = 0.643, 95%CI = 0.634 ~ 0.652); There is a negative correlation between weight loss and maximum oxygen uptake (B = −0.510, 95%CI = −0.537~−0.484); The year of novel coronavirus infection was positively correlated with the maximum oxygen uptake of adolescents (B = 0.116, 95%CI = 0.107~0.125). Conclusion This study shows that the impact of COVID-19 on BMI and heart and lung health in adolescents is significant. Young people of all ages and sexes showed similar developmental trends.